Health opportunities in Colombia (2017)
According to the theory of equality of opportunity, inequality in final outcomes (e.g., monetary income) is mainly caused by two broad characteristics: circumstances and individual effort. Individuals have no control on the former but on the latter. Inequalities in final outcomes caused by circumstances are considered unfair, while those generated by effort are not. In this paper, we calculate the level of unjust inequality in health in Colombia. A preliminary conclusion is that Colombia presents evidence of inequality of opportunities in health, which explains between 30% and 40% of total inequality in self-reported health status. Considering only observable circumstances, mother's health, household structure through childhood, and gender are individual characteristics that have considerable influence on this type of inequality. © 2017 Universidad de Antioquia. All rights reserved.